2019
DOI: 10.1155/2019/8425157
|View full text |Cite
|
Sign up to set email alerts
|

Resectability of Rectal Neuroendocrine Tumors Using Endoscopic Mucosal Resection with a Ligation Band Device and Endoscopic Submucosal Dissection

Abstract: Background Rectal neuroendocrine tumors (NETs) < 10 mm in diameter, limited to the submucosa without local or distant metastasis, can be treated endoscopically. Endoscopic mucosal resection with a ligation band device (EMR-L) and endoscopic submucosal dissection (ESD) have been employed to resect rectal NETs. We evaluated and compared the clinical outcomes of EMR-L and ESD for endoscopic resection of rectal NETs G1 < 10 mm in diameter. Methods We conducted a retrospective study of 82 rectal NETs in 82 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
1
26
0
2
Order By: Relevance
“…However, a sensitivity analysis of tumors <10 mm in the current study showed that ESD and EMR achieved similar en bloc resection, vertical and lateral margin involvement, complete resection, and recurrence. EMR may resect small tumors with comparable quality to ESD, which is also supported by findings from a previous meta‐analysis 45 . Thus, while existing guidelines 5,6 differ on how to manage rectal carcinoid tumors, this review suggests that both ESD and EMR are effective for treating rectal carcinoid tumors smaller than 10 mm.…”
Section: Discussionsupporting
confidence: 72%
“…However, a sensitivity analysis of tumors <10 mm in the current study showed that ESD and EMR achieved similar en bloc resection, vertical and lateral margin involvement, complete resection, and recurrence. EMR may resect small tumors with comparable quality to ESD, which is also supported by findings from a previous meta‐analysis 45 . Thus, while existing guidelines 5,6 differ on how to manage rectal carcinoid tumors, this review suggests that both ESD and EMR are effective for treating rectal carcinoid tumors smaller than 10 mm.…”
Section: Discussionsupporting
confidence: 72%
“…Lim et al. 15 reported that the lateral and VM were longer in the ESMR‐L group than in the ESD group. Kim et al.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports demonstrated that ESMR‐L achieved a complete resection rate not inferior to ESD. 13 , 14 , 15 However, ESD requires a longer procedure time and more advanced endoscopic techniques than ESMR‐L. Moreover, there are few reports comparing the results of different ER methods.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, ESMR-L once again outperformed C-EMR in terms of histologically complete resection (27/29, 93.1% vs. 82/110, 74.5%, P=0.03) for rectal neuroendocrine tumors with average size 7 mm, while at the same time the technique also showed valuable results in the long term [ 74 , 75 ]. Preliminary data suggested that the method even achieves at least equal resection outcomes to ESD for rectal carcinoid tumors <10 mm in size (complete resection rate 24/29, 82.8% vs. 25/31, 80.6% P=0.83) [ 76 ]; however, more recently it was shown that ESMR-L may in fact be even more superior to ESD for similar lesions, with respect to therapeutic outcomes and procedure time (95.5% vs.75.0%, P=0.02 for complete resection rate and 7.1±4.5 vs. 24.2±12.1 min, P<0.001, for resection time, respectively) [ 77 ]. In the largest prospective study comparing the efficacy and safety of the method and ESD for small rectal NETs (≤10 mm) [ 78 ], ESMR-L outperformed ESD, achieving a significantly higher pathological complete resection rate (53/53, 100% vs. 13/24, 54.2%, P<0.001).…”
Section: Emr With Band Ligation (Emr-l) or Endoscopic Submucosal Resection With Ligation (Esmr-l)mentioning
confidence: 99%